Ambivalent enmity: making the case for a transcultural turn in enmity studies : introduction - Becke, Johannes; Jaspert, Nikolas; Kurtz, Joachim (The journal of transcultural studies, 2023)
The introduction to this theme issue makes the case for a transcultural turn in enmitystudies. In view of the increase in conflict and polarization in both international anddomestic politics, the phenomenon of enmity needs to be studied from a freshperspective that fully recognizes its transcultural, processual, and deeply ambivalentfeatures. To sketch such an approach, we introduce and defend five hypotheses: (i)enmity is a driver of transculturation, not an obstacle; (ii) enmity describes a process, not an outcome; (iii) enmity is an expression of ambivalence, not of conclusiveness; (iv) the study of enmity requires a transdisciplinary approach; and (v) the study ofenmity needs historical depth. Case studies based on this perspective must integrateconcepts and methodological insights from the humanities and social sciences, and highlight the persistent links between enmity, understood as enduring forms ofpotentially violent antagonism, and ambivalence, defined as contradictory patterns ofemotions, values, and cultural habits. Without a deeper understanding of theambivalences of enmity, this theme issue argues, it is impossible to capture the dynamics of antagonism, past and present.
Gesehen am 04.06.2024